A Novel Variant in the TBC1D24 Lipid-Binding Pocket Causes Autosomal Dominant Hearing Loss: Evidence for a Genotype-Phenotype Correlation - Parzefall, Thomas; Frohne, Alexandra; Koenighofer, Martin; Neesen, Juergen; Laccone, Franco; Eckl-Dorna, Julia; Waters, Jonathan J.; Schreiner, Markus; Amr, Sami Samir; Ashton, Emma; Schoefer, Christian; Gstœttner, Wolfgang; et al. (Frontiers in Cellular Neuroscience, 2020)
Background: Hereditary hearing loss is a disorder with high genetic and allelic heterogeneity. Diagnostic screening of candidate genes commonly yields novel variants of unknown clinical significance. TBC1D24 is a pleiotropic gene associated with recessive DOORS syndrome, epileptic encephalopathy, myoclonic epilepsy, and both recessive and dominant hearing impairment. Genotype-phenotype correlations have not been established to date but could facilitate diagnostic variant assessment and elucidation of pathomechanisms. Methods and Results: Whole-exome and gene panel screening identified a novel (c.919A>C; p.Asn307His) causative variant in TBC1D24 in two unrelated Caucasian families with Autosomal dominant (AD) nonsyndromic late-onset hearing loss. Protein modeling on the Drosophila TBC1D24 ortholog Skywalker crystal structure showed close interhelix proximity (6.8Å) between the highly conserved residue p.Asn307 in α18 and the position of the single known pathogenic dominant variation (p.Ser178Leu) in α11 that causes a form of deafness with similar clinical characteristics. Conclusion: Genetic variants affecting two polar hydrophilic residues in neighboring helices of TBC1D24 cause AD nonsyndromic late-onset hearing loss. The spatial proximity of the affected residues suggests the first genotype-phenotype association in TBC1D24-related disorders. Three conserved residues in α18 contribute to the formation of a functionally relevant cationic phosphoinositide binding pocket that regulates synaptic vesicle trafficking which may be involved in the molecular mechanism of disease.